2015
DOI: 10.2174/1570162x13999150317155040
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis and Time Series Modeling Allow a Systematic Review of Primary HIV-1 Drug-Resistant Prevalence in Latin America and Caribbean

Abstract: Here we review the prevalence of HIV-1 primary drug resistance in Latin America and Caribbean using meta-analysis as well as time-series modeling. We also discuss whether there could be a drawback to HIV/AIDS programs due to drug resistance in Latin America and Caribbean in the next years. We observed that, although some studies report low or moderate primary drug resistance prevalence in Caribbean countries, this evidence needs to be updated. In other countries, such as Brazil and Argentina, the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…33 There are concerns, however, that PrEP could accelerate the transmission of drug-resistant HIV within particular regions where drugresistant HIV is already prevalent. 33,34 Recently, Abdulhaqq et al 35 showed that increased levels of IFNɛ gene and protein expression in the cervical epithelium correlated with reduced expression of genes associated with HIV-1 integration and replication, complementing our report of the direct antiviral actions of IFNε. At the same time, the findings of Veazey et al 36 on vaginal administration of IFNβ showed significant protection from simian/human immunodeficiency virus in macaques and contributed this to the upregulation of interferon response genes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…33 There are concerns, however, that PrEP could accelerate the transmission of drug-resistant HIV within particular regions where drugresistant HIV is already prevalent. 33,34 Recently, Abdulhaqq et al 35 showed that increased levels of IFNɛ gene and protein expression in the cervical epithelium correlated with reduced expression of genes associated with HIV-1 integration and replication, complementing our report of the direct antiviral actions of IFNε. At the same time, the findings of Veazey et al 36 on vaginal administration of IFNβ showed significant protection from simian/human immunodeficiency virus in macaques and contributed this to the upregulation of interferon response genes.…”
Section: Discussionsupporting
confidence: 78%
“…Currently, administration of pre‐exposure prophylaxis (PrEP) anti‐retroviral drugs is considered the most effective method for blocking transmission of HIV to uninfected individuals 33 . There are concerns, however, that PrEP could accelerate the transmission of drug‐resistant HIV within particular regions where drug‐resistant HIV is already prevalent 33 , 34 . Recently, Abdulhaqq et al 35 showed that increased levels of IFNɛ gene and protein expression in the cervical epithelium correlated with reduced expression of genes associated with HIV‐1 integration and replication, complementing our report of the direct antiviral actions of IFNɛ.…”
Section: Discussionmentioning
confidence: 99%
“…However, although encouraging, previous DC-based HIV-1 vaccination strategies have demonstrated limited abilities priming durable memory HIV-1-specific T cell responses (9)(10)(11)(12)(13). In addition, most vaccine studies used adjuvants systemically as a means to globally increase innate immune activation, without considering their individual impact on specific DC functional characteristics (14).…”
Section: Introductionmentioning
confidence: 99%